A unified approach for static and dynamic fracture failure in solids and granular materials by a particle method - Roberto Brighenti; Andrea Carpinteri; Nicholas Corbari (Fracture and Structural Integrity)
The material structure at the microscale reveals the particulate nature of solids. By exploiting the discrete aspect of materials, the so-called particle methods developed and applied to the simulation of solids and liquids have attracted the attention of several researchers in the field of computational mechanics. In the present paper, a particle method based on a suitable force potential is proposed to describe the nature and intensity of the forces existing between particles of either the same solid or different colliding solids. The formulation applies to problems involving both granular materials and solids interacting with granular materials. The above approach is applied to simulate different problems dealing with the 3D dynamic fracture and failure of solids.